THE LEADERSHIP STYLES AND MOTIVATION TOWARDS WORK ACHIEVEMENT - Maria, Anna (Universitas Kristen Indonesia, 2018)
Human resources (HR) is the central figure in an organization or company. In order for management activity goes well, the company should have employees who are knowledgeable and high berketerampilan as well as the effort to manage the company seoptimal possible so performance increases. The success of the organization can be achieved if employees are able to create a good working achievements are supported by the leadership style of superiors and the motivation is given. Within each activity must have a purpose, as for the purpose of this research is to know the relationship of leadership styles with the achievements of the work of employees. To find out the relationship with the work achievement motivation of employees. The research is descriptive-quantitative sample with as many as 30 employees and data analysis with SPSS analysis of Rank Spearman and T Test manually or statistical formulas. The results of this study suggest that (1) based on the results of the calculation obtained value t calculate of 3.241 and t table of 2.048 or t t > count table (3.241 > 2.048) so the then Ho is rejected and accepted which means there is Ha relationships significantly between leadership styles with the accomplishment of work. (2) calculation of the obtained results based on the value t calculate registration (5,267) greater than t table (2.048), Ho is rejected and accepted which means there is Ha relationship was significant between achievement motivation.Keyword: leadership styles, motivation, work achievement..